2D Seismic Reflection Study for Zubair Formation in East Nasiriya area, Southern Iraq - Faisal, Mohammed S.; Ali, Kamal K. (Iraqi Journal of Science, 2021)
An interpretive (structural and stratigraphic) study of the two,-dimensional seismic, data of East Nasiriya area (30 km to the south east of Nasiriya oil field within Thi-Qar province, southeastern Iraq) was carried out using Petrel 2017 program. The study area has an importance due to its location between many oil fields, but still without exploration of oil wells. Twenty five seismic lines were used, date back to different types of seismic surveys conducted in the region at different time periods. Also, the seismic velocity surveys of the nearest wells to oil fields, such as Nasiriya-1 and Subba-8, in addition to their sonic and density logs were used. A synthetic seismogram with a good matching with the seismic section was achieved to ensure the identification of the reflectors and reflectivity type (peak or trough) and follow up each one through the whole area of interest. Top Zubair reflector was picked using the composite line to link the seismic sections with each other after enhancing the ties between seismic lines. Time and depth maps were made using velocity maps created from the velocity model. The seismic, interpretation, in the area showed the existence of certain stratigraphic, features, in the ,studied reflector. Some distribution mounds and sand lenses were observed in the study area, which are continuous in more than two-dimensional seismic line in the area. These activity elements provide a reasonable explanation for the distribution of hydrocarbons in the area of study.